Admission Hyperglycemia in Head Injured Patients - Yousefzadeh Chabok Sh; Ahmadi Dafchahi M; Mohammadi H; Shabbidar S (Acta Medica Iranica, 2009)
Hyperglycemia, in trauma patient, is commonly associated with a hyper metabolic stress response. Our objective is to determine the effects of hyperglycemia on the overall outcome of head trauma patients. In this descriptive study data were collected from head trauma patients' admitted to Intensive Care Unit (ICU) of Poursina University Hospital in a one-year period (Jan 2004-Jan 2005), retrospectively. All patients had stayed in the ICU for more than 48 hours post-injuries. They were divided into two groups according to their serum glucose levels at the time of admission (<200mg/dl or >200mg/dl), age, gender and Injury Severity Score (ISS). Patients with diabetes mellitus were excluded .We determined the outcome according to duration of hospitalization and ICU stay as well as mortality rates. Variables were analyzed with t-test and chi square test. Out of 115 patients, 89.6% were men. About 36 % of patients had serum glucose levels ≥ 200 mg/dl over the study period and this group had significantly greater mortality rate but without necessarily longer ICU or hospital stay. In this study we have shown that admission hyperglycemia has significant effect on patient's mortality but it is still unclear whether it can be a cause for longer ICU/hospital stay."n© 2009 Tehran University of Medical Sciences. All rights reserved.